Implementasi BIM dengan Autodesk Revit 2025 pada quantity take-off material struktur Gedung Plaza Airlangga (Unair) tahap 1 terhadap volume - Dwi Nur Wahyudi; Masca Indra Triana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Rapid development in the construction sector is strongly influenced by its crucial and efficient functions. This drives the construction industry towards better integration. Currently, advances in technology and communication play an important role in overcoming various challenges, one of which is through the implementation of Building Information Modeling (BIM). This approach supports more integrated design and construction processes, resulting in higher efficiency. A primary challenge in construction service provision is the discrepancy in work volume, which can affect project success. By using Autodesk Revit 2025, the implementation of 5D BIM for material Quantity Take-Off can provide higher accuracy in volume estimation. In its implementation, data is processed using Autodesk Revit 2025 BIM software integrated with Microsoft Excel for further analysis. The results show that total volume calculations using Autodesk Revit are more precise compared to conventional methods. The volume of concrete work based on BIM is 2,005.35 m³, which is 83.31 m³ lower than the conventional method at 2,088.66 m³. Meanwhile, the reinforcement volume based on BIM is 354,670.98 kg, which is 29,024.91 kg lower than the conventional method at 383,695.89 kg. The contribution of this research is the demonstration that the implementation of 5D BIM using Autodesk Revit 2025 significantly improves the accuracy of structural work volume calculations compared to conventional methods, thereby helping to reduce volume discrepancies in construction projects and enhancing the reliability of material quantity planning.